Investigating Optimizing Mirror Orbits for Dark-side Illumination - Crawford-Taylor, Kaisa Elisabeth Anne (Proceedings of the Wisconsin Space Conference, 2019)
<span style="font-size: 10pt; font-family: 'Times New Roman'; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">When a planet is tidally locked with its star, the same side always faces the star; thus one side is always dark. This synchronization occurs quickly for potentially habitable Earth-like planets orbiting dim, low-mass stars. Korpela, Sallmen, & Leystra Greene (2015; KSG) suggest that advanced extraterrestrial civilizations may put large-scale mirror fleets in orbit around such exoplanets to reflect starlight to the dark side of the planet. They might also use such mirrors to alter the climate of their own or another planet. Radiation pressure (RP) will be important for such large, lightweight mirrors, but research on satellite orbit stability typically neglects its effects. The long-term goal of this research is to determine fuel-efficient satellite orbits in situations where RP is important. We use Python and REBOUND to simulate mirrors orbiting an Earth-like exoplanet in the habitable zone for a variety of stars. Our simulations use two settings: â€œAlways RPâ€ always reflects starlight towards the planetâ€™s center while â€œNighttime RPâ€ only does so on its dark side. We found mirrors survive longer when initially orbiting face on to the star compared to edge on. We present a selection of results illustrating how RP affects the mirrorâ€™s survival time.